Bioconversion of paper mill lignocellulosic materials to lactic acid using cellulase enzyme complex and microbial cultures - Mukhopadhyay, Achira (Kansas State University, 2009)
Paper mill sludge is a solid waste generated from the paper-making industry. Cellulose in the sludge can be hydrolyzed into glucose using a cellulase enzyme complex, which can then be fermented to produce value added chemicals, such as lactic acid. The enzyme requirement for hydrolysis of the cellulose in paper sludge was benchmarked against paper pulp. Enzymatic requirements for complete conversion of cellulose in paper pulp was found to be 12 fpu cellulase, supplemented with 5 egu of beta-glucosidase per gram of cellulose. However, beta-glucosidase supplementation had to be increased to 38 egu to obtain a similar level of hydrolysis in the case of paper sludge indicating a decrease in enzyme activity due to sludge components. Response Surface Methodology (RSM) was used to study the lactic acid yield from paper sludge using enzyme dosage and temperature as parameters and operating in simultaneous saccharification and fermentation (SSF) mode. Maximum lactic acid yield of 0.75 g/g glucose was obtained within 36 hours using 10 fpu cellulase supplemented with 32 egu beta-glucosidase at a temperature of 39 degree C. Using the optimization function of the software, the optimal operational conditions for paper sludge hydrolysis were found to be 9 fpu cellulase, 12.5 egu beta-glucosidase at 40 degree C which resulted in a lactic acid yield of 0.58 g /g glucose. Lactic acid producing microbial cultures, Lactobacillus plantarum and Rhizopus oryzae were evaluated for fermentation of the pulp and sludge hydrolyzate at 125-ml shake flask and 2-L fermenter levels. In paper pulp media, the yields obtained by bacterial and fungal fermentations were 0.89 and 0.36 g/g glucose, respectively. In the case of paper sludge, the yield remained same, but inhibition of bacterial growth occurred. This resulted in lower substrate uptake and productivity than those obtained in paper pulp. On the other hand, fungal growth rate was enhanced due to the high solids content of paper sludge. The yield of lactic acid from paper sludge using L. plantarum and R. oryzae was 0.88 and 0.72 g/g glucose, respectively. Microbial cultures native to the sludge were isolated and evaluated for their performance of lactic acid production.
Keywords: lactic acid; paper sludge; RSM; Environmental Sciences (0768)